Can IQ moderate the response to cognitive remediation in people with schizophrenia?. (January 2021) - Seccomandi, Benedetta; Agbedjro, Deborah; Bell, Morris; Keefe, Richard S.E.; Keshavan, Matcheri; Galderisi, Silvana; Fiszdon, Joanna; Mucci, Armida; Cavallaro, Roberto; Bechi, Margherita; Ojeda, Natalia; Peña, Javier; et al.
Abstract: Background: IQ and IQ decline are considered risk factors for poor prognosis in people with a diagnosis of schizophrenia. However, it is still not clear if, at least in part, IQ and IQ decline influence long-term outcomes via a negative effect on interventions. Aim: To identify whether current IQ, estimated premorbid IQ, or IQ decline moderate the response to cognitive remediation (CR). Method: Individual participant data from twelve randomised controlled trials of CR were considered. Hierarchical and k-means analyses were carried out to identify different IQ clusters. The moderating effect of estimated premorbid IQ, current IQ, and different IQ clusters (preserved, deteriorated and compromised trajectories) on cognitive outcomes at post-therapy and follow-up were evaluated using multiple linear regression. Results: Data from 984 participants (CR = 544, control = 440) with schizophrenia and schizoaffective disorders were considered. The sample had a mean current IQ of 84.16 (SD 15.61) and estimated premorbid IQ of 95.82 (SD 10.63). Current IQ moderated working memory outcomes: people with higher IQ had larger working memory gains after therapy compared to those with a lower IQ. Those with a preserved IQ had better cognitive outcomes compared to either the deteriorated or compromised IQ groups, and those with a deteriorated IQ had better outcomes compared to those in the compromised IQ group. Conclusion: Current IQ is a significant moderator of cognitive gains after CR. These findings highlight the need to evaluate whether therapy adaptations (e.g. offering more sessions) can attenuate this effect so that those with lower IQ may derive benefit similar to those with higher IQ.